Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/s100510050261
|View full text |Cite|
|
Sign up to set email alerts
|

Cavitation in superfluid helium-4 at low temperature

Abstract: Equation (42) should read:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 2 publications
7
41
0
Order By: Relevance
“…1,2 These experiments have shown that quantum cavitation takes over thermal cavitation at a temperature ͑T͒ around 200 mK, in good agreement with theoretical calculations, 3,4 so that the problem of cavitation in liquid 4 He can be considered as satisfactorily settled.…”
Section: Martí Pi and Manuel Barrancosupporting
confidence: 73%
“…1,2 These experiments have shown that quantum cavitation takes over thermal cavitation at a temperature ͑T͒ around 200 mK, in good agreement with theoretical calculations, 3,4 so that the problem of cavitation in liquid 4 He can be considered as satisfactorily settled.…”
Section: Martí Pi and Manuel Barrancosupporting
confidence: 73%
“…We have also studied the explosion of electron bubbles in the case of liquid 3 He. The capillary model of Sec.…”
Section: Electron Bubble Explosions In Liquid 3 Hementioning
confidence: 99%
“…This allows to address quantum cavitation, a phenomenon that may appear at very low temperatures. 3,5,6 Heterogeneous cavitation produced by impurities purposely introduced in the liquid is also interesting by itself, 7 and in a series of recent experiments the case of heterogeneous cavitation caused by electrons (electron bubble explosions) has been addressed in detail. 8,9,10 Another interesting case of heterogeneous cavitation in liquid 4 He thoroughly studied is that caused by the presence of quantized vortices acting as cavitation seeds.…”
Section: Introductionmentioning
confidence: 99%
“…These waves are quasi-spherical and, at the acoustic focus (the center), their amplitude can be very large. We used an optical method to detect the nucleation of bubbles by the negative swings of the waves [1,2]. This nucleation occurs beyond a certain threshold in the sound amplitude which needs to be determined as accurately as possible, in order to compare with independent theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%